2013
DOI: 10.4236/ajps.2013.412a2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tropical Algae as Additives on Rumen <i>in Vitro</i> Gas Production and Fermentation Characteristics

Abstract: Algae have become an area of intensive research in many fields of study. Areas of application are becoming increasingly diverse with the advent of technologies particularly in the mass production of algae biomass. Algae contain complex bioactive compounds and these are gaining importance in emerging technologies with nutritional and environmental applications. In this study, a preliminary investigation evaluated 15 species of algae from the major categories of marine and fresh water algae for their potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 34 publications
5
58
0
1
Order By: Relevance
“…The lower in vitro rumen degradation expressed in a lower rate and maximum cumulative gas production of the Ulva products compared to the reference feed materials are in agreement with results of Dubois et al (2013) and can be explained by the low NDF content and the relatively high content of ADL and protein. The fermentation of protein as substrate causes a lower gas production by the microbial fermentation compared to that of carbohydrates (Cone and van Gelder 1999).…”
Section: Discussionsupporting
confidence: 91%
“…The lower in vitro rumen degradation expressed in a lower rate and maximum cumulative gas production of the Ulva products compared to the reference feed materials are in agreement with results of Dubois et al (2013) and can be explained by the low NDF content and the relatively high content of ADL and protein. The fermentation of protein as substrate causes a lower gas production by the microbial fermentation compared to that of carbohydrates (Cone and van Gelder 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, some studies suggest that regardless of the compound used to decrease methane emissions, the basal diet fed to the animal plays an important role in the effectiveness of the compound. For instance, the supplementation of Oedogonium (0.2 g OM basis) to different basal substrates (1 g OM basis) has been found to decrease methane at different rates, by nearly 40%11, 30%12 or 15%13, when Rhodes grass (107 g kg −1 CP, 672 g kg −1 NDF, DM basis), Finders grass (27.5 g kg −1 CP, 746 g kg −1 non-structural carbohydrates, DM basis) or Rhodes grass hay (66.9 g kg −1 CP, 766 g kg −1 carbohydrates, DM basis), respectively, was used as basal substrate. Machado et al 13.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in a recent in vitro study, Dubois et al. () observed that algae with a very high level of protein content increased gas production in the rumen. Thus, it is clear that in vivo studies are required especially using microalgae with high protein content, such as Chlorella vulgaris, to determine their impact on methanogens population in the rumen.…”
Section: Introductionmentioning
confidence: 97%